A retrospective analysis of the clinical efficacy in patients treated with Alternaria alternata and Dermatophagoides farinae immunotherapy - Liu, Juan; Yin, Jia (Frontiers in Allergy, 2024)
BackgroundThe clinical efficacy of allergen-specific immunotherapy (AIT) for Alternaria alternata (A. alt) and Dermatophagoides farinae (Der f) extracts remains largely unknown in China. We sought to retrospectively evaluate the efficacy caused by AIT agents manufactured in China of patients who are sensitized to A. alt and Der f.MethodsPatients aged 5–27 years with asthma and perennial allergic rhinitis (AR), and AIT with A. alt and Der f were recruited, and then classified into two groups: A. alt-AIT (n = 31) and A. alt + Der f-AIT group (n = 39). All data were gathered retrospectively, including biological parameters, pulmonary function, and symptom and medication scores.Results70 patients who underwent A. alt and Der f AIT were enrolled. A significant improvement was observed in the values of FEV1% (P < 0.0001) and MEF 25 (P = 0.023) of lung function. Both the rhinitis symptoms and combined symptoms and medication scores for asthma decreased after AIT (by 45.3% and 80.3%, respectively, P < 0.0001 for each). Nearly 67% improvement rate (P < 0.0001) occurred in rhinoconjunctivitis quality of life, and a great increase existed in Asthma Control Test (ACT) score (P < 0.0001) after at least 1 year AIT, although there were no significant changes between these two groups. Besides, no significance was displayed in specific IgE to different allergens.ConclusionAIT with A. alt and Der f extracts had clinical efficacy for many patients in China, with a reduction of symptom and medication scores, and great improvement in spirometry function.